Factors Supporting Knowledge Integration in Global Innovation Projects: An Exploratory Study. Issue 4 (15th September 2013) - Baxter, David; Goffin, Keith; Szwejczewski, Marek
<x xml:space="preserve">Abstract</x> This exploratory study identifies the factors which contribute to effective knowledge integration in global innovation projects through an in‐depth analysis of two case studies. Knowledge integration is analysed in two components: knowledge (individual expertise), and integration (working together). Our analysis highlights three distinct ways that individuals think about individual expertise: individual knowledge and competence; feeling valued; and unfamiliar areas. We also identify four ways in which individuals think about working together: good social relations; cultural distance; negotiation skills; and better results through working with others. Using examples from the case studies, we discuss how these factors enable knowledge integration in globally distributed innovation projects. We also propose a model indicating how these factors impact on knowledge integration and innovation performance. This study contributes towards management guidance, which is currently lacking in the area of knowledge integration.